Determinants of commercial production of wheat in Nigeria: a case study of Bakura local government area, Zamfara State - A. Falola; B. A. Achem; W. O. Oloyede; G. O. Olawuyi (Trakia Journal of Sciences)
In Nigeria, wheat is a crop of both household and industrial importance. However, despite its good climatic and edaphic conditions, Nigeria still relies on massive wheat importation. This study therefore examined the factors influencing commercial production of wheat in Bakura Local Government Area (a wheat zone) of Zamfara State, Nigeria. Primary data were obtained from 210 wheat farming households and analyzed with descriptive statistics, household commercialization index (HCI) and tobit regression. The results showed that the average HCI was 54.7%, implying that there is a gap of 45.3% for the farmers to attain full commercialization level. Farm size, fertilizer, credit, access to improved varieties, age of household head, using man-power as the only source of labour for cultivation and non-farm income were found to significantly influence household commercialization of wheat production. The major constraints faced by the household vis-a-vis wheat production were low output price, inadequate land, lack of production inputs, high cost of inputs, transportation problem, inadequate credit facilities and diseases/pests. This study therefore recommends provision of inputs and credit to farmers, encouraging the youth to actively participate in wheat farming, encouraging wheat farmers through price support programmes as well as expanding farmland put to wheat cultivation.